2022
DOI: 10.1155/2022/9364467
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA FGD5-AS1 Regulates Bone Marrow Stem Cell Proliferation and Apoptosis by Affecting miR-296-5p/STAT3 Axis in Steroid-Induced Osteonecrosis of the Femoral Head

Abstract: Background. Osteonecrosis of the femoral head (ONFH) is a common hip joint disease, which is more harmful and seriously affects the lives of patients. This study aims to clarify the regulatory mechanism of lncRNA FGD5-AS1 in ONFH. Methods. The expression of the protein and mRNA was detected by RT-qPCR and Western blot assay. The regulatory mechanism of lncRNA FGD5-AS1 was detected by the dual-luciferase reporter assay, CCK-8 assay, and flow cytometry assay. Results. Dex can inhibit cell proliferation and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[35,36] Moreover, hsa-miR-296-5p directly targeted signal transducer and activator of transcription 3 (STAT3), inhibiting its mRNA and protein expression and reducing the proliferation and differentiation of bone marrow stem cells. [37] Unfortunately, hsa-miR-635 has been rarely studied, which explained why we failed to find its direct role played in the skeletal system. In one study, however, circRANBP17 was reported to up-regulate the expression level of runt-related transcription factor 2 (RUNX2) by sponging hsa-miR-635, promoting the proliferation and invasion of nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[35,36] Moreover, hsa-miR-296-5p directly targeted signal transducer and activator of transcription 3 (STAT3), inhibiting its mRNA and protein expression and reducing the proliferation and differentiation of bone marrow stem cells. [37] Unfortunately, hsa-miR-635 has been rarely studied, which explained why we failed to find its direct role played in the skeletal system. In one study, however, circRANBP17 was reported to up-regulate the expression level of runt-related transcription factor 2 (RUNX2) by sponging hsa-miR-635, promoting the proliferation and invasion of nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 92%
“…[35,36] Moreover, hsa-miR-296-5p directly targeted signal transducer and activator of transcription 3 (STAT3), inhibiting its mRNA and protein expression and reducing the proliferation and differentiation of bone marrow stem cells. [37]…”
Section: Discussionmentioning
confidence: 99%
“…The ceRNA mechanism also plays a key role in the classical axis OPG/RANK/RANKL that regulates osteoblast-osteoclast bone homeostasis. LncNORAD and lncFGD5-AS1, as ceR-NAs, target miR-26a-5p and miR-296-5p/STAT3, respectively, to regulate the major signaling pathways of osteoclast differentiation and bone resorption [18,65]. LncRNA/circRNA, as a ceRNA, is also involved in regulating other proliferation-and apoptosis-related pathways, including PI3K/Akt, Bad/Bcl-2, TGF-β, etc.…”
Section: Enhance Proliferation and Osteogenic Differentiationmentioning
confidence: 99%